2020
DOI: 10.1002/1878-0261.12754
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense‐mediated decay factor SMG7 sensitizes cells to TNFα‐induced apoptosis via CYLD tumor suppressor and the noncoding oncogene Pvt1

Abstract: Yang et al . found that mutation of the nonsense‐mediated decay factor SMG7 enhanced resistance to tumor necrosis factor (TNF)‐induced apoptosis via two oncogenic pathways. Downregulation of CYLD and overexpression of the long noncoding RNA Pvt1 converge to promote NF‐κB activation. The results indicate a composite tumor suppressor role for SMG7 in response to TNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…NMD regulates NF-kB also at different levels and SMG7 was identified as a determinant of resistance to TNF-induced extrinsic apoptosis induction [59]. Accordingly, its depletion was shown to prevent sensitivity to TNF and favor activation of the NF-kB pathway via reduction of tumor suppressor cylindromatosis CYLD [60], a deubiquitinase that cleaves polyubiquitin chains and is involved in TNF-induced necroptosis.…”
Section: Nmd As a Tumor Suppressor Interconnected With The Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…NMD regulates NF-kB also at different levels and SMG7 was identified as a determinant of resistance to TNF-induced extrinsic apoptosis induction [59]. Accordingly, its depletion was shown to prevent sensitivity to TNF and favor activation of the NF-kB pathway via reduction of tumor suppressor cylindromatosis CYLD [60], a deubiquitinase that cleaves polyubiquitin chains and is involved in TNF-induced necroptosis.…”
Section: Nmd As a Tumor Suppressor Interconnected With The Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…SMG7 is a nonsense-mediated decay complex protein, and is responsible for the surveillance and degradation of abnormal RNAs [ 28 ]. SMG7 may directly interact with p53, regulate p53 stability, and lead to p53-mediated DNA damage response [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that lncRNAs are involved in tumor development. [57][58][59][60][61][62] Nevertheless, the biological role and mechanism of lncRNAs in PCa BM remain largely undiscovered. As far as we know, PCAT6 was first systematically assessed in PCa BM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, revealing the precise mechanisms underlying BM and developing novel potential therapeutic targets are urgently needed for the prevention and treatment of BM. Emerging evidence has demonstrated that lncRNAs are involved in tumor development 57–62 . Nevertheless, the biological role and mechanism of lncRNAs in PCa BM remain largely undiscovered.…”
Section: Discussionmentioning
confidence: 99%